UPAYA PENCEGAHAN STUNTING DENGAN PEMBERIAN PROTEIN HEWANI MELALUI GERAKAN ONE DAY ONE EGG (SATU HARI SATU TELUR) TERHADAP SISWA SDN 03 KOTA METRO - Rohmatul Anwar; Asih, Diah Reni; Miftahudin Ahmad; Dwi Subakti Prastiyo; Ahmad Efendi (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
Stunting is a condition where children experience growth and development failure which can be caused by nutritional deficiencies. Community outreach activities focused on socializing stunting and prevention efforts through balanced nutrition consumption patterns can be one solution in reducing stunting. The one day one egg movement is a movement to give one egg per day to children. This movement can accelerate the addition of nutrients for children so that it can prevent stunting in children. Community service activities carried out by the UNU Lampung Animal Husbandry Lecturer Team in the form of socialization activities to prevent stunting through the One Day One Egg Movement at SD Negeri 03 Metro City. The socialization material that will be given is knowledge about stunting, prevention of stunting, the role of eggs in preventing stunting, and correct egg processing techniques. In addition, the distribution of boiled eggs to grade 2 students at SDN 03 Metro City through the One Day One Egg movement in the framework of UNU Lampung Animal Husbandry lecturers actively participating in stunting prevention.... Keywords: Stunting, Socialization, Egg